Comparative Quality Evaluation of Selected Brands of Cefuroxime Axetil Tablets Marketed in the Greater Accra Region of Ghana - Christina Osei-Asare; Esther Eshun Oppong; Frederick William Akuffo Owusu; John Antwi Apenteng; Yvonne Ochesinda Alatu; Robert Sarpong (The Scientific World Journal)
The ever-growing commercialization of poor-quality and substandard medicines, especially anti-infectives characterized by inadequate postmarket surveillance by stakeholders remains a major global health challenge, particularly in developing countries, where antibiotic drug resistance and its repercussions on human health remain dominant. This research sought to evaluate the pharmaceutical quality of six randomly selected brands of cefuroxime axetil tablets (250 mg) marketed in the Greater Accra region of Ghana. The selected brands were coded and subjected to both compendial and noncompendial tests. Statistical analysis and model-independent parameter (similarity factor, f2) were employed in analyzing the dissolution profiles of all the brands. All brands including the reference brand conformed to the pharmacopeial specifications for both compendial and noncompendial tests, indicating that they were of good quality. However, there were significant variations (p<0.05) in the disintegration time amongst the various brands. All the brands had ƒ2 values > 50 indicating similarity of their drug release profiles with the innovator. Hence, all the sampled cefuroxime axetil brands can be considered as pharmaceutical equivalents to the innovator drug. These brands can, therefore, be used as a substitute for the innovator drug by physicians to patients in cases of unaffordability or unavailability of the innovator brand.